The first-time homesteader : a complete beginner's guide to starting and loving your new homestead - Sowards, Jessica (Cool Springs Press, 2022)
The author guides you through the process of setting up your property (no matter how small or large), establishing a garden, welcoming animals into the fold, living more resourcefully, and expanding your homestead kitchen tools and skills with grace and confidence. Includes chapters on raising chickens, animal husbandry, growing a garden, home dairy production, bee keeping, resourceful living and homestead kitchen skills.